IMPROVING CLASS IX.2 STUDENTS’ NATURAL SCIENCE LEARNING OUTCOMES THROUGH EVERYONE IS A TEACHER HERE (ETH) STRATEGY AT SMPN 1 KAMPAR - Dewi Sari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper analyzes Grade IX.2 students’ low natural science learning outcomes at SMPN 1 Kampar, which aims to determine whether the use of the Everyone Is A Teacher Here (ETH) strategy can improve natural science learning outcomes at class IX.2 of SMPN 1 Kampar or not. The type of research is classroom action research (CAR) with the application of the Everyone Is A Teacher Here (ETH) strategy. The research subjects involved 25 students of Class IX.2 at SMPN 1 Kampar. The research is classroom action research, which was conducted in two cycles. Each cycle was conducted in two meetings, which consisted of planning, implementation, observation, and reflection. Based on the results of the analysis and discussion, it can be concluded that learning through the implementation of the Everyone Is A Teacher Here (ETH) strategy can improve students’ learning outcomes in Class IX.2 at SMPN 1 Kampar. The student’s absorption of the subject matter average score is high. In the first cycle, there were 21 students who got high scores and two students achieved very high scores. And it increased in the second cycle with 9 students who got very high scores. Classically, students’ learning completeness is declared complete with a percentage of 96.0%.